Faktor–faktor yang berhubungan dengan manajemen laktasi pada ibu menyusui yang bekerja di luar rumah - Sari, Putri Puspita; Aryawati, Wayan; Febriani, Christin Angelina (Holistik Jurnal Kesehatan, 2023)
Background: The coverage of exclusive breastfeeding in Lampung Province is 67.06 percent, the prevalence in South Lampung is 50.14 percent and the Tanjungsari Natar Health Center is 41.09 percent. Lactation management is an effort that mothers can make to achieve success in breastfeeding their babies.Purpose: To find out the factors related to lactation management for working mothers at the Tanjung Sari Natar Health Center in South Lampung in 2022.Method: Type of quantitative research with a comparative descriptive design. The population in this study were all working mothers who had children aged 6-24 months and residing in the working area of the Tanjung Sari Natar Health Center, South Lampung, consisting of 108 working mothers. The sampling technique uses total sampling. Data were analyzed by chi-square and logistic regression.Results: The results showed that there was a relationship between knowledge of exclusive breastfeeding (p value: 0.025 OR: 3.0), breastfeeding technique (p value: 0.033 OR: 2.53), knowledge of milking techniques (p value: 0.020 OR: 2.57) , husband support (p value: 0.002 OR: 0.26), health workers support (p value: 0.009 OR: 0.24) and family support (p value: 0.001 OR: 0.22) with lactation management of working mothers. There is no relationship between technical knowledge of storing, using expressed breast milk (p value: 0.081 OR: 0.46) and the general environment (p value: 1.000 OR: 1.00) with lactation management of working mothers. The most dominant variable was breastfeeding technique (p-value 0.003; B: 2.939).Conclusion: The factor that has the most influence on the lactation management of working mothers is the breastfeeding technique.Suggestion: It is recommended for health agencies to provide a consultation corner with competent counselors in the field of breastfeeding techniques.Keywords: Breastfeeding; Breast Milk; Lactation Management; Working Mothers.Pendahuluan: Cakupan ASI eksklusif di Provinsi Lampung yaitu sebesar 67,06 persen, prevalensi di Lampung Selatan 50,14 persen dan Puskesmas Tanjungsari Natar sebesar 41,09 persen. Manajemen laktasi adalah upaya yang dapat dilakukan ibu untuk mencapai keberhasilan dalam menyusui bayinya.Tujuan: Untuk mengetahui faktor-faktor yang berhubungan dengan manajemen laktasi ibu pekerja di Puskesmas Tanjung Sari Natar Lampung Selatan Tahun 2022.Metode: Jenis penelitian kuantitatif dengan desain deskriptiif komparatif. Populasi dalam penelitian ini seluruh ibu pekerja yang memiliki anak 6-24 bulan dan bertempat tinggal di wilayah kerja Puskesmas Tanjung Sari Natar Lampung Selatan sebanyak 108 ibu pekerja. Teknik pengambilan sampel menggunakan total sampling. Data dianalisis dengan chi-square dan regresi logistik.Hasil: Hasil penelitian menunjukkan ada hubungan pengetahuan ASI ekslusif (p value: 0,025 OR: 3,0), teknik menyusui (p value: 0,033 OR: 2,53), pengetahuan teknik memerah (p value: 0,020 OR: 2,57), dukungan suami (p value: 0,002 OR: 0,26), dukungan nakes (p value: 0,009 OR: 0,24) dan dukungan keluarga (p value: 0,001 OR: 0,22) dengan manajemen laktasi ibu pekerja. Tidak terdapat hubungan antara pengetahuan teknik menyimpan, menggunakan ASI perah (p value: 0,081 OR: 0,46) dan lingkungan umum (p value: 1,000 OR: 1,00) dengan manajemen laktasi ibu pekerja. Variabel yang paling dominan adalah teknik menyusui (p-value 0,003; B: 2.939).Simpulan: Faktor yang paling berpengaruh terhadap manajemen laktasi ibu pekerja adalah teknik menyusui.Saran: Disarankan untuk instansi kesehatan agar disediakannya pojok konsultasi dengan konselor yang kompeten dibidang teknik menyusui.